Implementasi Transformasi Digital dan Kecerdasan Buatan Sebagai Inovasi Untuk UMKM pada Era Revolusi Industri 4.0 - R, Mardiana; Fahdillah, Yosi; Kadar, Melani; Hassandi, Irfan; R, Mandasari (LPPM Universitas Dinamika Bangsa, 2024)
Abstract−Technology plays an important role in economic development. Covid-19 has changed people's lifestyles and the behavioral patterns of business actors have transformed from traditional to digital. Even though Covid-19 has had a significant impact in the form of a decline in the global economy, including on Micro, Small and Medium Enterprises (MSMEs), it has also provided lessons in the form of adaptation to innovation and digital transformation in the form of the application of the latest technology and artificial intelligence. In line with the industrial revolution 4.0 and digital transformation, it can provide opportunities and strengths to build sustainable businesses. Along with changes in people's consumption patterns, MSMEs have also implemented digital adoption in the form of switching to e-commerce platform sites, food delivery applications and online business models. However, the adoption of artificial intelligence is still not widely used by MSMEs. However, several MSMEs have adopted artificial intelligence technology such as chatbot applications for communication services. Apart from that, support and providing programs from the government and the private sector are needed for MSMEs so that they can develop and adapt their business models to the latest technological adaptations so that MSMEs are also able to survive and even grow rapidly in the future.Keywords: Industrial Revolution 4.0, Digital Transformation, Artificial Intelligence, MSMEs